(untitled) (UUM Journal of Legal Studies, 2023)
Omnibus legislation isthe crucial method used when enacting the Law on Job Creation and it is concerned with providing further protection for Indonesia workers.Ibis article aims to identify the new regulations pertaining to the Job Creation Law, especially in the Labor cluster. In addition, this article will also try to analyze the relevant labor cluster regulations of the Job Creation Law, paying special attention to the issue of legal protection for workers. This is normative legal research that has applied the statutory approach, conceptual approach, and factual approach. The findings of the research show that there are various changes related to labor issues in the Job Creation Law, including regulations related to foreign workers, work relations, working time, rest and leave time, wages, termination of employment, and severance pay.An analysis of the legal implication that arises from several indicators of change then shows that the characteristics of the Labor Cluster arrangement in the Job Creation Law are potentially detrimental to workers. Although several new regulations benefit workers in an industrial relationship, in general, the Job Creation Law, especially the Labor Cluster, still reflects the main orientation of its formation, namely to facilitate investment through the creation of a :flexible working relationship, causing uncertainty and the more marginalized status of workers. There is a need to ensure further certainty in the laws in order to ensure a broader protection for the status and rights of Indonesian workers.